Entre arte e sentidos : um estudo sobre os sentidos emergentes no processo de um grupo de arte – identidade - Câmara, Cândida Maria Farias (2011)
This research comes from the commitment made by its author in the Movement of Community Mental Health of Bom Jardim (MCMHBJ), a nongovernmental organization that acts in Fortaleza into the neighbourhood named Grande Bom Jardim. Our previous integration in this instituition is to develop team works with the identity art setted down the deployment of the research process.Our aim is to understand the senses that comes out from those ones involved, in the creativy process, in an art identity group of MCMHBJ, checking the direction which points in identity building. Specifically, identifing the senses expressed by the participiants from the art identity; checking the aspects from the identity expression that exists in these built senses andanalysing the contribuition of art utilization to the fortifying of identity. For that, the methodology ease-searching was utilizated and it was carried out with the ones involved in the group, adults from 21 to 59 years old, two verbal closeness and photography registration as instruments to collect datas that were submitted to the content analysis. Our research ascertained the presence of five units of sense: fears and resistances to creation; processes of creation; existential polarity of the axis liberation/borning and prision/banings; nature and feeling of group and gratitude. And it’s concluded that the identificated senses reveal that the creative process mediated by art as a form to fortify the identity in the necessary transformations and in the developing of their creativity and courage to create. Even ahead of repression and shifting of the creativity notion, the factors of group bond and nature contact mediated by art can provide to insert these difficulties to get them over. The art has its fundamental rule which is to provide the emergence of the love-identity.